Proteomic analysis of microtubule-associated proteins during macrophage activation. - Patel, P; Fisher, K; Yang, E; Deane, C; Harrison, R (2009)
Classical activation of macrophages induces a wide range of signaling and vesicle trafficking events to produce a more aggressive cellular phenotype. The microtubule (MT) cytoskeleton is crucial for the regulation of immune responses. In the current study, we used a large scale proteomics approach to analyze the change in protein composition of the MT-associated protein (MAP) network by macrophage stimulation with the inflammatory cytokine interferon-gamma and the endotoxin lipopolysaccharide. Overall the analysis identified 409 proteins that bound directly or indirectly to MTs. Of these, 52 were up-regulated 2-fold or greater and 42 were down-regulated 2-fold or greater after interferon-gamma/lipopolysaccharide stimulation. Bioinformatics analysis based on publicly available binary protein interaction data produced a putative interaction network of MAPs in activated macrophages. We confirmed the up-regulation of several MAPs by immunoblotting and immunofluorescence analysis. More detailed analysis of one up-regulated protein revealed a role for HSP90beta in stabilization of the MT cytoskeleton during macrophage activation.